Are boys and girls that different? An analysis of traumatic brain injury in children. Issue 8 (8th September 2012) - Collins, Niamh C; Molcho, Michal; Carney, Peter; McEvoy, Linda; Geoghegan, Lourda; Phillips, Jack P; Nicholson, Alf J
Abstract : Introduction: The Phillips Report on traumatic brain injury (TBI) in Ireland found that injury was more frequent in men and that gender differences were present in childhood. This study determined when gender differences emerge and examined the effect of gender on the mechanism of injury, injury type and severity and outcome. Methods: A national prospective, observational study was conducted over a 2-year period. All patients under 17 years of age referred to a neurosurgical service following TBI were included. Data on patient demographics, events surrounding injury, injury type and severity, patient management and outcome were collected from 'on-call' logbooks and neurosurgical admissions records. Results: 342 patients were included. Falls were the leading cause of injury for both sexes. Boys' injuries tended to involve greater energy transfer and involved more risk-prone behaviour resulting in a higher rate of other (non-brain) injury and a higher mortality rate. Intentional injury occurred only in boys. While injury severity was similar for boys and girls, significant gender differences in injury type were present; extradural haematomas were significantly higher in boys (p=0.014) and subdural haematomas were significantly higher in girls (p=0.011). Mortality was 1.8% for girls and 4.3% for boys. Conclusions: Falls were responsible for most TBI, the home is the most common place of injury and non-operable TBI was common. These findings relate to all children. Significant gender differences exist from infancy. Boys sustained injuries associated with a greater energy transfer, were less likely to use protective devices and more likely to be injured deliberately. This results in a different pattern of injury, higher levels of associated injury and a higher mortality rate.